Aplicación de ejercicios kinestésicos en habilidades motrices en escolares de la Unidad Educativa Juan de Velasco - Mayra Gissela, Siguencia cruz (2021)
ABSTRACT The use of this intelligence is very varied, influenced by adaptation to the environment and the individual's goals. Therefore, those who acquire this intelligence achieve better information processing through bodily sensations (Sosa and Amparo 2018). This point will not be taken into account within the educational system from any perspective, where the learning process must be integral. It becomes essential to implement alternatives or technical development to get this intelligence better. Consequently, this research establishes that kinesthetic exercises are linked to motor skills, using test techniques and evaluation instruments. With the obtained results, it will be possible to be promoted in the Physical Education programs of the elementary sublevel for good early development of motor skills. Finally, an analysis is made and related to similar research within the sciences of Physical Education, where the actual incidence in its development and integral formation of the student is identified; therefore, it allows promoting and creating techniques that can or should be used within our early childhood or pre-school educational system. Keywords: kinesthetic exercises, kinesthesia, motor skills. Reviewed by: MsC. Hugo Romero R. ENGLISH PROFESSOR c.c 0603156258